Influence of Duration of Heroin Dependence on Humoral Immunologic Indicators. Issue 6 (November 2016) - Simonovska, Natasha; Zafirova-Ivanovska, Beti; Babulovska, Aleksandra; Pereska, Zanina; Jurukov, Irena; Trenchevska-Siljanovska, Liljana
Abstract : Objective: The incidence of autoantibodies may be associated with the duration of drug use. In this study, we assessed the association between the duration of heroin dependence and various humoral immunologic indicators, including IgA, IgG, IgM, complement component 3, complement component 4, rheumatoid factor, anti-β2-glycoprotein 1 (IgA, IgG, IgM), antinuclear antibody, circulating immune complexes, and cryoglobulins. Methods: A total of 363 patients with heroin dependence were enrolled in this cross-sectional and prospective study over a 3.5-year period. Depending on the duration of heroin use, participants were divided into 3 groups: up to 3 years, 4 to 7 years, and more than 7 years of heroin dependence. All patients were analyzed for the indicators. Results: There was a significant difference between the duration of heroin dependence and increased concentration of IgA ( P = 0.0000), IgG ( P = 0.0000), IgM ( P = 0.0001), complement component 3 ( P = 0.042), rheumatoid factor ( P = 0.0001), anti-β2-glycoprotein 1 (IgA, P = 0.0098; IgG, P = 0.0000; IgM, P = 0.0000), the presence of antinuclear antibody ( P = 0.01) and cryoglobulins ( P = 0.0000), and decreased concentration of complement component 4 ( P = 0.002). There was no significant difference in circulating immune complex concentration ( P = 0.097). Conclusions: A longer duration of heroin dependence was associated with increased concentrations of IgA, IgG, IgM, complement component 3, rheumatoid factor, anti-β2-glycoprotein 1 (IgA, IgG, IgM), presence of antinuclear antibodies and cryoglobulins, and decreased concentrations of complement component 4, but there was no influence on circulating immune complex values.